ВЛИЯНИЕ ЭКСТРАКТОВ ЛЕКАРСТВЕННЫХ РАСТЕНИЙ НА БИОЛОГИЧЕСКИЕ СВОЙСТВА МИКРООРГАНИЗМОВ (Experimental biology, 2017)
The results of investigation of the effect of plant extracts (salsokollin, ekdifit, aterolid, saussalin, grossgemin, Arglabin native, pinostrobin) and essential oils (ayafrol and eferol) on the biological properties of microorganisms presents this article. These drugs were studied at different concentrations (from 0,000032 to 0,02 g / ml) on the index of viability and biological activity of Lactobacillus fermentum, Staphylococcus aureus, Streptococcus pyogenes, Escherichia coli and Klebsiella ozaenae.
Keywords: plant extracts; essential oils